Faktor Penentu Setting Fisik Dalam Beraktifitas Di Ruang Terbuka Publik â€œStudi Kasus Alun â€“ Alun Merdeka Kota Malangâ€ - Adhitama, Muhammad Satya (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2013)
The development of a town center in an effort to improve the quality of the social environment and community can be seen from the existence of public open space and how much use, because the future availability of public open space will be increasingly difficult to obtain , so it is important to plan the existing public spaces being lost due to lack of use the space for the community and the surrounding environment. This research took a case study in the Malang Merdeka square. Where the condition of Malang Merdeka square current arrangement functioned more as a green open space in the city center of the space to accommodate its use as a public activity. For that we need a physical setting arrangement square that can function either as a green space and can accommodate the public in the city center . This study aims to identify determinants of physical activity in the setting of public open space. The foundation of the theory used in this study is public open space , behavior settings , environment and behavior . The method used in this research is descriptive qualitative . The subjects were the main users - Malang Merdeka square , the data collection method using a place - centered and person- centered mapping mapping . The results showed that the arrangement of the physical setting in a public space , can affect the behavior of the user in the activity in the square - square .Keywords : Behavior, Utilization, Physical Setting, Public open space .